Vascular fingerprint and vascular damage markers associated with vascular events in testicular cancer patients during and after chemotherapy. (August 2016) - Lubberts, S.; Boer, H.; Altena, R.; Meijer, C.; van Roon, A.M.; Zwart, N.; Oosting, S.F.; Kamphuisen, P.W.; Nuver, J.; Smit, A.J.; Mulder, A.B.; Lefrandt, J.D.; et al.
Abstract: Background: Metastatic testicular cancer (TC) can be cured with bleomycin, etoposide and cisplatin (BEP) chemotherapy. This comes at the price of an increased cardiovascular disease risk, not only years afterwards, but also during and shortly after chemotherapy. To prevent cardiovascular events, high-risk patients should be identified. The aim of this study was to assess BEP-chemotherapy induced vascular damage and to find risk factors for early vascular events. Patients and methods: A prospective cohort study was performed in (B)EP treated TC patients. Development of venous and arterial vascular events was assessed. Vascular damage markers (von Willebrand factor [vWF], coagulation factor VIII [FVIII], intima media thickness [IMT]) and cardiovascular risk factors were assessed before and until 1 year after chemotherapy. Before start of chemotherapy a vascular fingerprint was estimated. Presence of ≥3 risk factors was defined as high-risk vascular fingerprint: body mass index >25 kg/m 2, current smoking, blood pressure >140/90 mm Hg, total cholesterol >5.1 and/or low-density lipoprotein >2.5 mmol/L or glucose ≥7 mmol/L. Results: Seventy-three patients were included. Eight (11%) developed vascular events (four arterial events, four pulmonary embolisms). vWF and FVIII increased during chemotherapy, especially in patients with vascular events. Sixteen patients (22%) had a high-risk vascular fingerprint before start of chemotherapy. These patients had arterial events more often (3/16 [19%] versus 1/57 [2%]; p = 0.031) and higher vWF levels and IMT. Conclusions: Endothelial activation and upregulation of procoagulant activity seem important mechanisms involved in early (B)EP-chemotherapy-induced vascular events. Before chemotherapy, a quarter already had cardiovascular risk factors. A vascular fingerprint could identify patients at risk for arterial events. This vascular fingerprint, when validated, can be used as a tool to select patients who may benefit from preventive strategies. Highlights: Bleomycin, etoposide and cisplatin-chemotherapy induces endothelial activation and procoagulant activity. Endothelial activation and procoagulant activity seem involved in early onset vascular disease. The course of von Willebrand factor and coagulation factor VIII may be helpful in detecting patients at risk for early vascular events. Cardiovascular risk factors already are prevalent in testicular cancer patients before start of chemotherapy. A high-risk vascular fingerprint can identify patients at risk for early arterial vascular events.